Selecting the Most Adequate Bedding Material for Broiler Production in Brazil - Garcia, R. G.; Almeida Paz, I. C. L.; Caldara, F. R.; Naeaes, I. A.; Pereira, D. F. [UNESP]; Ferreira, V. M. O. S. (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2012)
Broiler chicken production is widely dispersed across the globe, and one important issue for growers is the selection of adequate bedding material, as the availability and price of substrates varies among countries and regions within a same country. This study aimed at applying a multiple criteria analysis approach for the selection of the most appropriate bedding material for broiler production. Based on field research data and growers' experience, the most desirable characteristics of a litter material were chosen as the main criteria. The selected materials were wood shavings, rice husks, chopped Napier grass ( Pennisetum pupureum), 50% sugar cane bagasse ( Saccharum L.) plus 50% wood shavings, 50% sugar cane bagasse ( Saccharum L.) plus 50% rice husks, and pure sugar cane bagasse ( Saccharum L.). The analytical hierarchy process ( AHP) was applied for selecting the most suitable bedding material. Validation was performed using data from previous studies carried out in central-western Brazil on the effects of different types of bedding material on broiler carcass quality. Considering the selected criteria, several bedding materials were tested and ranked, and the results showed that wood-shavings litter was the best option (weight = 0.28), followed by rice husks (weight = 0.24). All other tested alternatives presented lower scores and were, therefore, not considered for use. The AHP approach was found to be an efficient tool to select the most appropriate litter material under specific scenarios.
Keywords: Alternative bedding material; broiler production; multiple criteria analysis; AHP